PRAKTIK MACHIAVELLIAN BERBASIS GENDER MAHASISWA AKUNTANSI DARI PESPEKTIF SEMIOTIKA - Totanan, Chalarce; Arista, Arista; Yamin, Nina Yusnita; Abdulllah, Muhammad Ikbal; Muliati, Muliati; Indriasari, Rahayu (Widya Mandala Surabaya Catholic University, 2022)
Research Purposes. The study aims is to analyze Machiavellian practices in accounting students based on gender by feminine and masculinity.Research Method. This research based with Roland Barthes's semiotic paradigm. Data were obtained through interviews and involving themselves in the lecture and exam processes. Informants are accounting students were randomly selected.Research Result and Findings. Machiavellian practice in denotation findings reveals that student actions are rule in written regulations, while the connotation reveals that the practice based on courage, solidarity, perfectionist and sensitivity level in carrying out the action of Machiavellian practices on accounting students. The meaning of myth in Barthes semiotics departs on the connotation meaning, where this study reveals that femininity and masculinity play a role for students in carrying out Machiavellian practices. The findings of this research, that when each student wants brilliant achievement so that he uses an improper method.